'Chance Tourism': Lucky enough to have seen what you will never see. (June 2018) - Zerva, Konstantina
The quest for tourist destinations that few have visited, and the experience of a journey that few can share, is becoming even more difficult for those individuals who seek a reputation as tourists. Although this search for authenticity has already been studied, there is still much to be explored. Tourists can enhance their identity as travellers by place attachment with destinations they have visited, and that no longer exist. The fact that these destinations have vanished makes their experiences unrepeatable, turning them into connoisseurs of a gone place. The narration of that past visit enters into a re-interpretation process, especially by those who have not been to these places. Through this transformation of the visit into a chance event, this article shows the connection between chance, tourism and social spatialization. Through a content analysis approach, visitors' online comments to three tourist sites are used: the World Trade Centre in New York before 9/11, the historical sites of Nepal before the destructive earthquake of 2015 and the 'Pioneer Cabin Tree', a giant thousand-year-old sequoia in Calaveras Big Trees State Park, before it was blown down in a storm in 2017.